Factors Influencing Work–Life Balance in Physicians and Advance Practice Clinicians and the Effect of Heartfulness Meditation Conference on Burnout. (January 2019) - Thimmapuram, Jayaram R; Grim, Rodney; Bell, Theodore; Benenson, Ronald; Lavallee, Mark; Modi, Mihir; Noll, David; Salter, Ridgley
Background: Burnout levels have risen in recent years and satisfaction with work–life balance has decreased. Individual and organizational factors may affect burnout in physicians and advance practice clinicians (APCs). Meditation is a tool to mitigate stress and enhance well-being. In this study, we assessed the factors affecting work–life balance in physicians and APCs. We also measured the impact of Heartfulness meditation conference on burnout. Methods: Physicians and APCs were surveyed through an abbreviated Maslach burnout inventory (aMBI) to assess the burnout levels and a question to assess the factors influencing work–life balance. Wellness initiatives included either attending a Heartfulness meditation conference or reading a book about burnout and wellness (approximated at a 3-h read). A repeat aMBI survey was sent 8 weeks after the conference. Pre- and postburnout scores were assessed. Results: Of the 1393 physicians and APCs, 537 responded to the aMBI, and there were 414 comments (663 factors) for the question on work–life balance. Among the respondents, 60.5% and 32% had symptoms of moderate to severe emotional exhaustion (EE) and depersonalization, respectively. Twenty-eight percent of the respondents had symptoms of moderate to low personal accomplishment. The major factors impacting work–life balance included work load, work flow, and scheduling. A follow-up aMBI survey was completed by 79 from the conference group and 264 from the nonconference group. In the age-group between 30 and 50 for the conference group (n = 40), mean EE decreased from 9.8 to 8.6 with statistical significance ( P = .014). There was no statistically significant change in the nonconference group in any age-group. Conclusion: Workload, workflow, and scheduling issues were the major factors affecting work–life balance. There is a significant level of burnout in physicians and APCs. Heartfulness meditation conference was associated with a significant decrease in EE in those aged 30 to 50 years. There was no significant change seen in the nonconference/book reading group.